COVID-19 Countering Policy: Latest Polemics in Indonesia - Prasetya, Rizki Agung (The Indonesian Journal of International Clinical Legal Education, 2020)
Nowadays in Indonesia even in the world there is an epidemic in the form of a virus, Viruses are microscopic (super-small) organisms that are spread all over the world and tend to be parasitic. Almost all ecosystems in the world contain viruses and are considered as the most numerous organisms on planet Earth. Viruses can infect living things, ranging from humans, animals, plants, fungi, and even bacteria. Many of these viral infections have fatal consequences for the creatures they infect. Viruses also cannot replicate (reproduce themselves) without riding on other organisms. For this reason, viruses are classified as parasitic or harmful organisms. This virus is called corona or commonly referred to as COVID 19, this virus is a virus similar to MERS and SARS that attacks the respiratory tract, this virus first appeared or was detected in one of the regions in China, namely Wuhan City, this virus spread very quickly throughout China and even the world even the World Health Organization WHO establishes this virus as a global pandemic, Pandemic refers to a disease that spread to many people in several countries at the same time.